Behavior of stainless steel–reinforced concrete piers under lateral impact loading. (May 2017) - Zhang, Guoxue; Xu, Shixiang; Xie, Hongbing; Zhou, Xiwu; Wang, Yingfeng
In this study, stainless steel bars with the same diameter were used to replace ordinary stressed steel bars in reinforced concrete bridge piers. An ultra-high drop hammer impact test system was adopted for multiple horizontal impact tests on two groups of reinforced concrete bridge pier specimens. Based on the study results, it was determined that the maximum impact force of the stainless steel–reinforced concrete specimen, strain occurred in the steel bar and concrete, and the maximum displacement at the specimen's top was found to be smaller than that before the same diameter replacement under the same impact energy. These results indicate that the stainless steel–reinforced concrete bridge pier specimen may have strong ductility, energy absorption abilities, and impact resistance under the impact load.